The satisfied proscribed: Victor Hugo's exile works - Callipo, Daniela Mantarro [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2017)
Although Victor Hugo supported the candidacy of Louis Napoleon in the elections for president of the French Republic and helped to elect him in 1848, Hugo turned against Bonaparte after the coup d'etat in December of 1851. The opposition to the government resulted in an exile wich only finished 19 years later, with the decay of Napoleon III. Victor Hugo produced nonstop for all these years: Napoleon le Petit, Les Chatiments, Les Contemplations, Les Travailleurs de la Mer, Les Chansons des Rues et des Bois, La Legende des siecles, Les Miserables, William Shakespeare, Les Travailleurs de la Mer e L'Homme qui rit are examples of an arduous and inspired work, but that doesn't hide the sadness of the exile. This article aims to analyze the texts that Victor Hugo wrote during or after his banishment in order to comprehend in wich way it influenced his work.
Keywords: Victor Hugo; Exile; Literary works of exile; Coup d'etat; Louis Napoleon